Synthesis and Biological Evaluation of 3-Amidoquinuclidine Quaternary Ammonium Compounds as New Soft Antibacterial Agents - Renata Odžak; Doris Crnčević; Antonio Sabljić; Ines Primožič; Matilda Šprung (Pharmaceuticals, 2023)
Quaternary ammonium compounds (QACs) are among the most effective antimicrobial agents that have been used for more than a century. However, due to the growing trend of bacterial resistance and high toxicity of QACs, research in this field remains a pressing matter. Recent studies of the structure–activity relationship suggest that the introduction of the amide functional group into QAC structures results in soft variants that retain their antimicrobial properties while opening the possibility of fine-tuned activity regulation. Here, we report the synthesis and structure-function study of three structurally distinct series of naturally derived soft QACs. The obtained 3-amidoquinuclidine QACs showed a broad range of antibacterial activities related to the hydrophobic-hydrophilic balance of the QAC structures. All three series yielded candidates with minimal inhibitory concentrations (MIC) in the single-digit <semantics>μ</semantics>M range. Time-resolved growth analysis revealed subtle differences in the antibacterial activity of the selected candidates. The versatile MIC values were recorded in different nutrient media, suggesting that the media composition may have a dramatic impact on the antibacterial potential. The new QACs were found to have excellent potential to suppress bacterial biofilm formation while exhibiting low ability to induce bacterial resistance. In addition, the selected candidates were found to be less toxic than commercially available QACs and proved to be potential substrates for protease degradation. These data suggest that 3-amidoquinuclidine QACs could be considered as novel antimicrobial agents that pose a low threat to ecosystems and human health.